PENGUKURAN KINERJA PEMELIHARAAN JALAN REL DENGAN METODA OMAX - Simamora (NIM : 25099068), Marsinta
Abstract : Performance can be defined as a level of achievement of goal as aratio of output and target and how good a source can be used to achieve a certain result or output (1)J . Sumanth,1984) The aims of this research are to identify parameters the track maintenance performance of Regional Operation level (REOP) PT.KAI and to measure the p rkmnance of track maintenance quantitatively by using Objective Matrix (OMAX) method. Literally and field research (datas seeunder observation) can be indentity the performance parameters of track maintenance in Regional Operation (REOP) PT.KA1, they are : the indicator of decreasing and increasing of railway quality category very good_ (VG), Good (G), Fair (F) and Poor (P) anad also unit cost indicator before and after maintenance. From performance measuring have been done, it show that performance of REOP I, lit and IV rnr all periode of measurement ( 5 semester) is hi .her than standar performance, has mean the performance i, satisfied anal consistent While REOP II,V,VI,VII,VIII and IX are very Iluctt ated, whereas duriags performance measurement same performance periode are lower than standard performance and go higher than unconsistent performance indicated that has been standardize From indicator weight analisys, it shows that performance maintenance will tindery decrease when cost parameter weight of maintenance iuerease linicry. The performance will reach the highest value when maintenance cost parameter has weight 0 % and in neverse performance will reach the lowest value when the maintenance cost 100 % . From sensitivity analysis result of performance parameters it show that decreasing or increasing unit cost of me parameter is not sensitive. It caused by maintenance cost allocated (budget) eguivalen with actual cost.